2019
DOI: 10.26714/mki.2.3.2019.97-104
|View full text |Cite
|
Sign up to set email alerts
|

Murottal Therapy Lowers Blood Pressure in Hypertensive Patients

Abstract: The incidence of hypertension always increasing every year, the incidence of hypertension increased from 25,8% to 34.1% in 2018. The Hypertension’s patients were prone to psychological problems for example stress that could raise the blood pressure. The intervention non-pharmacological for lowering blood pressure is using intervention murottal. This study aims to analyze the influence murottal’s therapy to decrease blood pressure in hypertension’s patients in the community health center Bandarharjo. The design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 3 publications
0
2
0
9
Order By: Relevance
“…The pain will appear again after the reaction from the drug wears off, so the patient has to wait for the next drug administration hour according to the predetermined hour. 3,4 In this study, it showed that the decrease in the average pain intensity of the intervention group was higher than the control group with a difference in the mean reduction of 1.55 with a p-value of 0.009 (pvalue <0.05), this means that there is a difference in the decrease in intensity. pain relief after being given a combination of murottal Al-Quran therapy and virtual reality in the intervention group than in the control group in postoperative patients.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The pain will appear again after the reaction from the drug wears off, so the patient has to wait for the next drug administration hour according to the predetermined hour. 3,4 In this study, it showed that the decrease in the average pain intensity of the intervention group was higher than the control group with a difference in the mean reduction of 1.55 with a p-value of 0.009 (pvalue <0.05), this means that there is a difference in the decrease in intensity. pain relief after being given a combination of murottal Al-Quran therapy and virtual reality in the intervention group than in the control group in postoperative patients.…”
Section: Discussionmentioning
confidence: 53%
“…After five hours post-injection, the drug concentration in the blood decreases, as a result of which the analgesic effect of the drug decreases. 3,4 Pain that arises as a result of tissue damage is subjective and causes discomfort. 5 Pain is a physiological mechanism that aims to protect yourself and as a warning sign that tissue damage is occurring, therefore, assessment of pain by nurses in postoperative patients is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Tekanan darah sistolik sebelum dilakukan intervensi didapatkan rata-rata 153,50 mmHg, setelah Laili Fatmawati -Penurunan Tingkat Kecemasan pada Pasien Pre Operasi Sectio Caesarea dengan Terapi Murotal dan Edukasi Pre Operasi This work is licensed under a Creative Commons Attribution 4.0 International License. dilakukan intervensi rata-rata 129,50 mmHg (Irmachatshalihah & Armiyati, 2019). Lantunan ayat yang diterima oleh telinga dikirimkan ke amigdala kemudian sinyal dilanjutkan ke hipokampus yaitu bagian otak yang berfungsi untuk proses pengolahan emosi seseorang yang berisi tentang motivasi yang mendorong otak untuk mengingat pikiran, pengalaman yang menyenangkan dan tidak menyenangkan.…”
Section: Pembahasanunclassified
“…Bacaan al-Qur'an secara murottal dipilih dalam penelitian ini karena mempunyai irama yang konstan, teratur dan tidak ada perubahan yang mendadak. Tempo murottal al-Qur'an juga berada antara 60-70/menit, serta nadanya rendah sehingga mempunyai efek relaksasi dan dapat menurunkan stress dan kecemasan (Yueniwati, 2016 (Irmachatshalihah & Armiyati, 2019).…”
Section: Pembahasanunclassified